2014
DOI: 10.1017/s1355617714000010
|View full text |Cite
|
Sign up to set email alerts
|

Mild Cognitive Impairment: A Concept and Diagnostic Entity in Need of Input from Neuropsychology

Abstract: This virtual issue consists of studies previously published in the Journal of the International Neuropsychological Society and selected on the basis of their content related to one of the most highly researched concepts in behavioral neurology and neuropsychology over the past decade: mild cognitive impairment (MCI). The reliance on cognitive screening measures, staging-based rating scales, and limited neuropsychological testing in diagnosing MCI across most research studies may miss individuals with subtle co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 48 publications
0
53
0
4
Order By: Relevance
“…Functional changes are currently assessed in combination with genetic, neurobiological, neuroimages and cognitive behavioral indicators as one of the risk factors in dementia (Bondi & Smith, 2014;Albert et al 2011).…”
mentioning
confidence: 99%
“…Functional changes are currently assessed in combination with genetic, neurobiological, neuroimages and cognitive behavioral indicators as one of the risk factors in dementia (Bondi & Smith, 2014;Albert et al 2011).…”
mentioning
confidence: 99%
“…Indeed, a key advantage of this study was the statistical determination of MCI subtypes using a core group of well researched neuropsychological tests (Libon et al, 2010(Libon et al, , 2014. Thus, MCI subtypes were determined empirically using neurocognitive constructs well known to be affected in both dementia and MCI (Bondi & Smith, 2014;Libon et al, 2014). Previous research has shown evidence for the presence of both singledomain impairments (i.e., amnestic and dysexecutive) and multi-domain MCI subtypes (Delano-Wood et al, 2009;Libon et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Several common clinical diagnostic criteria for the diagnosis of MCI have been proposed (Petersen, 2004;Winblad et al, 2004). Recently, literature has emerged using person-centered statistical modeling techniques to classify patients with MCI (see Bondi & Smith, 2014, for a review). Research using person-centered statistical modeling techniques to classify patients with MCI has generally been consistent in that patients with singledomain (amnestic/dysexecutive) as well as multi-domain syndromes can be identified (Delano-Wood et al, 2009;Libon et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…파킨슨병의 진행 과정에서 경도 인지장애(mild cognitive impairment. MCI)와 치매를 명 확하게 정의하는 것은 어려움이 따르지만 경도인지장 애는 동일 연령과 교육 수준에 비하여 인지 기능은 저 하되었으나 치매와는 달리 기초적인 생활을 스스로 수행할 수 있거나 전반적 사회 활동에 명백한 지장을 초래하지 않는다는 점에서 구분 할 수 있다 [7] . (magnetic resonance image.…”
Section: 파킨슨병은 뇌신경 전달 물질인 도파민 결핍이 70%unclassified